Hubungan Sikap Ibu dan Dukungan Suami dengan Kejadian Hiperemesis Gravidarum Grade II-III - Limra Limra; Andi Parellangi; Elisa Goretti (Journal of Pharmaceutical and Health Research, 2023)
Hyperemesis gravidarum, which often occurs in the early stages of pregnancy, can be quite disruptive. However, the majority of pregnancy-related nausea and vomiting can be managed with outpatient care and the use of antiemetic medications. In this context, social support, especially from spouses, and the mother's attitude toward hyperemesis gravidarum symptoms can play a role in preventing further development of this condition. This research was conducted to examine the relationship between the mother's attitude and spousal support with the occurrence of Grade II-III hyperemesis gravidarum at the Kaubun Health Center in 2023. The research method used was a correlation study with a cross-sectional approach. The study population involved 32 first-trimester pregnant women who visited the Kaubun Health Center in January 2023, and the entire population was sampled. The results of the statistical analysis using the chi-square test indicated a significant relationship between the mother's attitude (p-value = 0.000) and spousal support (p-value = 0.006) with the occurrence of hyperemesis gravidarum. Therefore, the conclusion of this research is that the mother's attitude and spousal support are associated with the occurrence of Grade II-III hyperemesis gravidarum at the Kaubun Health Center in 2023. Husbands play a crucial role in providing support, understanding, and positive feelings to wives experiencing hyperemesis gravidarum, helping wives feel comfortable and capable of managing these symptoms. A deeper understanding of this condition enables husbands to provide more effective support, contributing to the prevention and management of hyperemesis gravidarum during pregnancy.